Benzothiazole-Based Bis-azo Cationic Fluorescent Dyes with Extended Conjugated Systems: Synthesis and Properties - Nourmohammadian, Frahnaz; Alikhani, Mohammad Yousef; Gholami, Mahnaz Davoudzadeh; Abdi, Ali Ashtiani (Journal of Applied Solution Chemistry and Modeling, 2015)
Sixteen novel 2-aminobenzothiazole based dichromophoric cationic azo dyes were synthesized and their photophysical properties studied. The colors of the synthesized azo dyes were violet to blue with high molecular extinction coefficient ranged between 2.6 - 4.7— 104 (M-1.cm-1). All of the dyes showed unique fluorescence emission at a broad range of 409â€“494 nm. The absorption and emission spectral changes of selected dyes were also analyzed in solvents with different polarity. Furthermore, the antibacterial activities of the dyes were evaluated against gram positive and negative bacteria including S. aureus, S. epidermidis, E. coli, and P. aeruginosa and different concentrations of dyes showed an anti-gram positive bacterial activity.